The impact of audit committee expertise on audit quality: Evidence from UK audit fees. Issue 6 (November 2017) - Ghafran, Chaudhry; O'Sullivan, Noel
Abstract: Governance regulators currently place great emphasis on ensuring the presence of financial expertise on audit committees (Sarbanes-Oxley, 2002; UK Corporate Governance Code 2010–2016). Underlying this is a belief that greater expertise enhances the effectiveness of audit committees and, by extension, the quality of the external audit. This study investigates the impact of audit committee expertise on one measure of audit quality - audit fees paid by FTSE350 companies. Our analysis finds that audit committees possessing greater levels of financial expertise are associated with higher audit fees. When we segregate financial expertise between accounting and non-accounting, we find that the positive impact identified is driven by non-accounting expertise. Furthermore, when we separate FTSE100 and FTSE250 firms we find the impact of financial expertise is confined to FTSE250 firms. Our findings are important as they highlight the usefulness of segregating financial expertise between specialists and non-specialists, something which regulators in the UK and in the USA currently do not do. Our findings also highlight the potential value of audit committee expertise in smaller as opposed to larger listed firms, suggesting that the value of expertise to audit quality depends on the specific financial reporting challenges firms face.